Epigenetic memory contributing to the pathogenesis of AKI-to-CKD transition - Tanemoto, Fumiaki; Nangaku, Masaomi; Mimura, Imari (Frontiers in Molecular Biosciences, 2022)
Epigenetic memory, which refers to the ability of cells to retain and transmit epigenetic marks to their daughter cells, maintains unique gene expression patterns. Establishing programmed epigenetic memory at each stage of development is required for cell differentiation. Moreover, accumulating evidence shows that epigenetic memory acquired in response to environmental stimuli may be associated with diverse diseases. In the field of kidney diseases, the “memory” of acute kidney injury (AKI) leads to progression to chronic kidney disease (CKD); epidemiological studies show that patients who recover from AKI are at high risk of developing CKD. The underlying pathological processes include nephron loss, maladaptive epithelial repair, inflammation, and endothelial injury with vascular rarefaction. Further, epigenetic alterations may contribute as well to the pathophysiology of this AKI-to-CKD transition. Epigenetic changes induced by AKI, which can be recorded in cells, exert long-term effects as epigenetic memory. Considering the latest findings on the molecular basis of epigenetic memory and the pathophysiology of AKI-to-CKD transition, we propose here that epigenetic memory contributing to AKI-to-CKD transition can be classified according to the presence or absence of persistent changes in the associated regulation of gene expression, which we designate “driving” memory and “priming” memory, respectively. “Driving” memory, which persistently alters the regulation of gene expression, may contribute to disease progression by activating fibrogenic genes or inhibiting renoprotective genes. This process may be involved in generating the proinflammatory and profibrotic phenotypes of maladaptively repaired tubular cells after kidney injury. “Priming” memory is stored in seemingly successfully repaired tubular cells in the absence of detectable persistent phenotypic changes, which may enhance a subsequent transcriptional response to the second stimulus. This type of memory may contribute to AKI-to-CKD transition through the cumulative effects of enhanced expression of profibrotic genes required for wound repair after recurrent AKI. Further understanding of epigenetic memory will identify therapeutic targets of future epigenetic intervention to prevent AKI-to-CKD transition.